HUBUNGAN ANTARA EQUALITY BEFORE THE LAW DALAM PENEGAKAN HUKUM DI INDONESIA DENGAN HARMONISASI KONFLIK ANTAR LEMBAGA PENEGAK HUKUM - DADIN EKA Saputra (Syariah: Jurnal Hukum dan Pemikiran, 2015)
This paper aims to analyze the relationship between the application of the legal principle ofequality before the law in law enforcement in Indonesia with the harmonization of conflict between thestate institutions and the National Police Commission. The method used in this research is normativejuridical, namely research in the review by reference and based on the norms and rules of law, thelegislation in force, theories and doctrines of law, jurisprudence, and materials other literature relevantto the research topic. From the analysis of the data, it can be concluded that there is a recognition of theprinciple of normative and empirical rule of law, namely that all the issues are resolved with the law asthe supreme guidance. Normatively either in the Constitution of the Republic of Indonesia Year 1945,and in Undang-Undang Nomor 39 Tahun 1999 on Human Rights, the principle of equality of treat-ment before the law has been published in a comprehensive manner, as the rights that must be re-spected, guaranteed, protected and met by the state. Disharmony between institutions or law enforce-ment agency that is now emerging, should be immediately solved by basing the legislation that exists.